Agro-Economic Effect of Georgian and European Beekeeping Market (Vallis Aurea, 2019)
The European Union has expanded a number of times throughout its history by way of the accession of new member countries to the Union. Former USSR republic of Georgia and the EU have maintained relations since 1996. The government expressed a desire to become a member state of the EU. To enhance their relationship, the EU and Georgia have signed several agreement in recent years. EU encourage Georgia to further approximate with European legislation and standards and initiated the process of supporting Georgian economy for further integration into EU. In recent years the European Union has been supporting rural and agricultural development of Georgia, the country with the the longest history of beekeeping and honey production. On 27 June 2014, The European Union and Georgia signed an Association Agreement. The agreement introduced a preferentialtrade regime – the Deep and Comprehensive Free Trade Area. Based on having better-matched regulations, this regime increases market access between the European Union and Georgia. In this work, alongside with statistics and brief history, we present our view of the future of this cooperation which can be based not only on export of honey to the EU market, but the Georgian Bee itself. It is estimated that pollinators, mainly honey bees, contribute at least 22 billion EUR each year to the European agriculture industry. They ensure pollination for over 80% of crops and wild plants in Europe. In recent years the quality and area of pollination in Europe has been decreasing. These issues can greatly benefit from the specific characteristics only Georgian Bee is known for, like longest tongue (proboscis) and exceptional gentleness. We strongly believe, that due to various strengths and features only this specie boasts, the export of Georgian Bees will lead to very fruitful collaboration for both parties.